(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The insurance industry in India has passed through aperiod of structural changes under the combined impact of financial sectorreforms in general and insurance sector in particular. The market for insuranceservices previously was monopolistic while the market place was regulated andinsurance companies were expected to receive assured spreads over their costsof funds and systematic demand for their products. This phase in insurancebusiness was the result of sheltered markets and administered prices forvarious insurance products.